The quality of education as a modern paradigm of preparing future specialists for speciality “Preschool Education” - Іншаков, Артур (Pedagogy of Higher and Secondary Education, 2014)
Inshakov A. Ye. The quality of education as a modern paradigm of preparing future specialists for speciality “Preschool Education”. The article is devoted to issues concerning improving grades and the quality of education while training preschool teachers in the course “The modern Ukrainian language workshop”. The suggested system of work and forms of control will help to form language skills that are necessary for a teacher.